Development and Evaluation of Microemulsion-Based Sunscreen Cream Containing Lycopene from Tomato (Solanum lycopersicum L.) - Ritha Pratiwi; Nandiska Maladjili; Evi Sulastri; Yusriadi Yusriadi; Nuur Aanisah; Armini Syamsidi (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
This study aimed to formulate and determine the sun protection factor (SPF) of sunscreen made from tomato lycopene microemulsion creams. Lycopene was used as the active ingredient with varying concentrations in each formula, namely F1 5%, F2 7.5%, and F3 9%. The preparation of each formula was evaluated by conducting the globule size, polydisperse index, organoleptic test, homogeneity test, pH test, spreadability test, viscosity test, and determination of SPF value. The average globule size was 119 nm which had a uniform size distribution. The physical characteristics test of the cream preparations showed the three had a bright yellow color and lacked odor. The pH test results were 3.2 ± 0.12, 5.54 ± 0.25, 6.48 ± 0.22 for F1, F2, F3, respectively. Viscosity test results were F1 40,893.33 cPs, F2 41,746.67 cPs, and F3 43,106.67 cPs. The values obtained from the dispersion test were F1 6.71±0.63, F2 5.58±0.15, and F3 4.81±0.11. Moreover, F3 with a concentration of 9% tomato lycopene microemulsion met the acceptance criteria for all of the physical properties including low viscosity to promote good spreadability, pH that does not irritate the skin, aesthetic appeal, small particle size, and non-odorous and an SPF value of 4.9. The obtained microemulsion-based sunscreen cream exhibited a good physical property of lycopene besides showing sufficient SPF value.